Growth and reproduction of earthworm in organic waste mixtures and effects on chemical and microbial properties of vermicompost - Zibetti, Volnei Knopp; Nachtigal, Glaucia de Figueiredo [UNESP]; Lima, Daniel Lopes de; Schiedeck, Gustavo (Interciencia, 2015)
There is a large demand for organic fertilizers in organic agriculture, but few options for different wastes have been studied. The aim of the present work was to evaluate the biological responses of earthworms Eisenia andrei Bouche in wastes composed of cattle manure, peanut husk and spent coffee grounds, as well as to analyze the effect of earthworms on the microbial density and chemical properties of the vermicompost. Four treatments were employed, H1: cattle manure (100%), H2: cattle manure (75%) + peanut husk (25%), H3: cattle manure (75%) + spent coffee grounds (25%), H4: cattle manure (50%) + spent coffee ground (25%) + peanut husk (25%), with six replicates in a completely randomized design. The addition of spent coffee grounds to the manure increased the total biomass and indicated a rising trend in the production of cocoons, while the peanut husk apparently did not affect these variables. The CFU of bacteria and fungi were affected by the treatments at the beginning and end of the experiment and by the earthworms during the waste transformation. The evaluated organic waste mixtures differently affected the growth and reproduction of earthworms and chemical and biological properties of humus.
Crescimento e reprodução de minhocas em misturas de resíduos orgânicos e efeitos nas propriedades químicas e microbiológicas do húmus